Effect of tomato and red guava juice on blood glucose level in overweight woman - Aghnia Ilma Izzati; Mohammad Jaelani; Yuwono Setiadi; Enny Rahmawati; Yulianto Yulianto (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Based on the results of Riskesdas 2018 that the prevalence of diabetes mellitus in Indonesia showed an increase from 6.9% to 8.5%. Overweight is closely related to impaired blood glucose, insulin resistance, and decreased insulin secretion. Preventive efforts that have been made using non-pharmacological treatments, such as increasing the intake of fiber and lycopene from fruits.Objectives: This study aimed to determine the effect of tomato juice and guava juice on blood glucose levels in overweight women.Materials and Methods:  The study design is a true experiment conducted in 11subjects in treatment group and 11 subjects in control group. The subject of this study were overweight adult women 45-55 years. Blood sampling was taken in the morning, then glucose levels were measured using the GOD-PAP method (Glucose Para Amino Phenazone). We gave 600 ml of tomato juice and red guava every day for 21 days. To find the effect of juice on fasting blood glucose levels controlled by nutrient intake and physical exercise using the Repeated Measure ANOVA test.Results: In the treatment group, there was a decrease of 3.24 mg/dl in blood glucose levels; while, in the control group, the decrease in blood glucose levels was only 0.26 mg/dl. However, we found no statistically significant differences in both groups.Conclusions: Consumption of tomato juice and red guava reduced fasting blood glucose.